2022
DOI: 10.1002/agt2.173
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐phase molecular self‐assembly facilitated supramolecular films with alternative hydrophobic/hydrophilic domains for skin moisture detection

Abstract: Human skin moisture is closely related to health and personal care issues. Many creams were developed to claim capable of skin moisturizing. However, people can hardly check their skin moisture status and the moisturizing effect of various creams conveniently, since currently all the skin moisturizing detection rely on large equipment requiring power supply. Herein, we report a power-supply independent supramolecular film that is able to directly report the moisturizing status of the skin. With the strategy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…These distances are about 2 times of the increasing length of the corresponding surfactants (SDS ≈ 1.7 nm, SDeS ≈ 1.5 nm). FT-IR measurements (Figure b) revealed that the symmetric and asymmetric vibration band for the alkyl chains in the PDDA-SDS and PDDA-SDeS films occurred at 2852, 2922, and 2854, 2924 cm –1 , respectively, manifesting the alkyl chains packed less orderly as it becomes shorter. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These distances are about 2 times of the increasing length of the corresponding surfactants (SDS ≈ 1.7 nm, SDeS ≈ 1.5 nm). FT-IR measurements (Figure b) revealed that the symmetric and asymmetric vibration band for the alkyl chains in the PDDA-SDS and PDDA-SDeS films occurred at 2852, 2922, and 2854, 2924 cm –1 , respectively, manifesting the alkyl chains packed less orderly as it becomes shorter. , …”
Section: Resultsmentioning
confidence: 99%
“…Under mild mechanical pressure and in the presence of physically adsorbed water to facilitate molecular rearrangement, the caking in the PE/surfactant precipitates leads to a self-supporting supramolecular film, where the surfactant bilayers were bridged by the PE chains to form continuous macroscopic structures. This not only allows the preparation of noncolloidal form self-supporting macroscopic molecular self-assembled materials but also makes it possible to get diversified functions. ,,, ,,, However, we found that the film formation ability and the resultant mechanical strength of the film depend highly on the surfactant and polyelectrolyte structure, in particular, the surfactant chain length and the molecular weight of the PE. In order to reveal the physical insight behind this effect, herein, we report a systematic study of the films formed with sodium alkyl sulfates and poly dimethyl diallyl ammonium chloride (PDDA).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Compared to other techniques, excited-state processbased [26][27][28][29] and small molecule-related [30][31][32][33] fluorescent techniques, especially those based on fluorescent films, [34][35][36][37][38][39][40][41][42][43] demonstrate great sensitivity, improved selectivity, and unprecedented designability. For film-based fluorescent sensors, however, the films must be highly porous and photochemically stable, as they are necessary for sensitive, reversible, and applicable sensing.…”
Section: Introductionmentioning
confidence: 99%
“…17−19 Therefore, a thorough understanding of intricate dynamic interplays between mitochondria and lysosomes might provide insights into the underlying mechanisms of many diseases and pave the way for the development of novel therapeutic strategies. Organic small-molecule fluorescent probes are currently recognized as powerful tools in the field of highly sensitive detection 20,21 and live-cell imaging. 22,23 Remarkably, they facilitate the visualization and analysis of organelle dynamics and interactions.…”
mentioning
confidence: 99%